Keterampilan Guru SD Dalam Menghadapi Era Revolusi Industri 4.0 - Dede Salim Nahdi; Ujiati Cahyaningsih (Universitas Sebelas Maret, 2019)
One of the great challenges of Indonesian society in the era of the industrial revolution 4.0 is globalization, where globalization can lead to greater competition in all areas of people's lives, including education. The teacher as the spearhead of education is the most important element in an education system. Student learning processes are strongly influenced by teacher competence. Teachers have a strategic role in the field of education, even other sources of adequate education are often meaningless if not supported by the presence of qualified teachers. The basic ability to read, write and count absolutely is no longer enough to be able to compete in the era of the industrial revolution 4.0 which is full of challenges. Education must be able to prepare students to compete in the global community. For this reason, teachers must be able to adapt to all forms of change. In the era of the industrial revolution 4.0, where all educational activities and even the joints of life are inseparable from the use of digital technology, teachers must have some skills to deal with cultural change in this fast-paced era